Prognostic significance of beat-to-beat variability of spatial heterogeneity of repolarisation analysed from 5-minute resting electrocardiogram in coronary artery disease - Perkiomaki, J; Rahola, J T; Mattila, S M; Kiviniemi, A M; Ukkola, O H; Tulppo, M P; Junttila, M J; Huikuri, H V; Kentta, T V (Europace (London, England), 2024)
Abstract Background Data on the prognostic significance of temporal variability of spatial heterogeneity of electrocardiographic repolarisation in coronary artery disease (CAD) are limited. Purpose To evaluate the prognostic value of temporal variability of T-wave morphology analysed from 5-minute resting ECG in CAD. Methods The standard deviation (SD) of T-wave morphology dispersion (TMD-SD), the SD of T-wave heterogeneity (TWH-SD), and the SD of total cosine R-to-T (TCRT-SD) were analysed on beat-to-beat basis from a 5-minute period of resting 12-lead ECG obtained before a clinical stress test in 1702 patients with angiographically verified CAD and well-preserved left ventricular function. Results During an average of 8.7±2.2 years of follow-up, 60 (3.5 %) patients experienced sudden cardiac death (SCD) or were resuscitated from a sudden cardiac arrest (SCA), 69 (4.1 %) patients experienced non-sudden cardiac death (NSCD), and 161 (9.5 %) patients died due to non-cardiac death (NCD). TMD-SD was significantly higher in patients who experienced SCD/SCA compared with those without such an event (1.72 ± 2.00 vs. 1.12 ± 1.75, p= 0.01, respectively) and in patients who succumbed to NSCD compared with those without such an event (1.57 ± 1.74 vs. 1.12 ± 1.76, p=0.04, respectively), but did not differ significantly between patients who experienced NCD and those without such an event (1.16 ± 1.42 vs. 1.14 ± 1.79, p=0.86, respectively). After adjusting for relevant clinical risk factors in the Cox multivariate hazards model, TMD-SD retained its significant association with the risk of SCD/SCA (HR 1.119, 95 % CIs 1.015–1.233, p=0.024), but not with the risk of NSCD (HR 1.089, 95 % CIs 0.983–1.206, p=0.103). Conclusion TMD-SD, representing temporal variability of spatial heterogeneity of electrocardiographic repolarisation, is independently associated with the long-term risk of SCD/SCA in CAD patients with well-preserved left ventricular function.